Determination of fluorescence lifetimes of fluorescein from fluorescence quenching data - Ogunsipe, Abimbola; Opeolu, Olutunji (International Journal of Advanced Chemistry, 2020)
The fluorescence quenching of fluorescein by 1,4-benzoquinone (BQ) in five solvents – methanol, ethanol, phosphate buffer saline (PBS, pH 7.4), N,N'-dimethylformamide (DMF) and dimethylsulphoxide (DMSO) is hereby investigated. Fluorescein’s fluorescence was effectively quenched by BQ, and the quenching was dynamic (purely collisional) within the BQ’s concentration range (0.001 to 0.004 M) used in this work. Accordingly, the quenching data were in conformity with the Stern-Volmer’s model. Stern-Volmer’s constant (KSV) values range between 17.4 in DMSO and 43.4 in methanol. KSV values, together with the calculated bimolecular rate constants (kD) in the respective solvents, were used to semi-empirically estimate the fluorescence lifetimes (tF) of fluorescein in the individual solvents. Just as for KSV values, tF values are solvent-viscosity dependent, with the lowest values being obtained in methanol and the highest in DMSO, which are the least and most viscous solvents respectively. tF values obtained in this work are 3.55, 3.71, 3.78, 4.13 and 4.51 ns (in methanol, PBS 7.4, ethanol, DMF and DMSO, respectively).
Keywords: Fluorescein; Benzoquinone; Fluorescence; Quenching; Lifetime.